Analisis Perhitungan Produktivitas Alat Berat Gali-Muat (Excavator) dan Alat Angkut (Dump Truck) pada Pekerjaan Timbunan Maindam Bendungan Bulango Ulu - Mohamad Nurbachri Eraku; Arfan Usman Sumaga; Mohammad Yusuf Tuloli (Research Review: Jurnal Ilmiah Multidisiplin, 2025)
Heavy equipment plays a crucial role in ensuring the smooth and timely execution of construction projects. Inaccurate analysis of heavy equipment productivity and poor selection of equipment can lead to project delays and cost inefficiencies. This study aims to analyze the productivity of heavy equipment used in the main embankment work of the Bulango Ulu Dam, determine the estimated duration of work completion, and evaluate alternative efficiency strategies. A descriptive qualitative approach was employed, with a focus on excavators and dump trucks used in four categories of embankment excavation work: core, fine filter, coarse filter, and rock. The results show that the productivity of excavators in core embankment excavation reached 790.65 m³/hour, with a work duration of 69 days, while dump trucks recorded 820.50 m³/hour with 66 days of work. For fine filter embankment excavation, excavators achieved 779.24 m³/hour (32 days), and dump trucks 530.40 m³/hour (48 days). In the coarse filter embankment excavation, excavator productivity remained at 779.24 m³/hour (34 days), while dump trucks reached 511.20 m³/hour (52 days). In rock embankment excavation, excavator productivity was 898.00 m³/hour (394 days), and dump trucks 561.20 m³/hour (631 days). Based on the efficiency comparison, Alternative 2 is recommended as it provides a significant reduction in project duration with a relatively minimal cost increase compared to Alternative 1. These findings highlight the importance of accurate equipment planning to optimize project performance in terms of time and cost.